Position Estimation of Multiple Receiving Coils and Power Transmission Control for WPT without Feedback - Heo, Jun; Kim, Sang Won; Cho, In Kui; Park, Yong Bae (Energies, 2022)
It is important to determine the position of the receiver (Rx) coils in wireless power transfer (WPT) system, and to control the power transmitted to the Rx coil based on this result. In particular, in a situation where there is no feedback between the primary side and the secondary side, it is difficult to control the received power because the information is limited. In this paper, a method for determining the position of the Rx coils and controlling the received power using limited parameters in a feedback-free WPT system is proposed. The proposed method is verified by constructing a (Formula presented.) WPT system, and it is validated that the simulation result and the experimental result are consistent well. Furthermore, arbitrary power can be transmitted to the Rx coil based on the result of the position of the Rx coil. The experiment is conducted by transmitting about (Formula presented.) to Rx 1 and Rx 2, and the efficiency for Rx 1 is about (Formula presented.), Rx 2 is (Formula presented.), and the overall efficiency is confirmed to be (Formula presented.).
Keywords: No feedbacks; Position estimation; Power; Power transfer systems; Power transmission control; Power-control; Received power; Receivers (Rx); Receiving coil; Receiving power; magnetic resonance; no feedback; position estimation; power control; wireless power transfer